Mechanical Properties Of Pack Carburized AISI 4340 With Variation Energizer Composition of Barium Carbonate (BaCO3) And Sodium Carbonate (Na2CO3) - Agris Setiawan; Sapna Yusmania; Anton Sudiyanto (Universitas Sebelas Maret, 2023)
This research aimed to determine the mechanical strength of American Iron and Steel Institute (AISI) 4340 steel after pack carburizing with a combined variation of barium carbonate (BaCO3) and sodium carbonate (Na2CO3) as an energizer. Combination of two variations of energizer materials as an alternative to improve mechanical properties. The various ratios of energizer: 40/60, 50/50, and 60/40% w/w. The mechanical test was conducted to determine tensile (American Society for Testing and Material-ASTM E-8), impact strength (ASTM E-23), Rockwell hardness (ASTM E-18), and microstructure characterization (ASTM E-3). Both type specimens were temperature pack carburized was 950 ℃, and the holding time was 3 hours. Results showed that Specimen C had the lowest ultimate tensile strength mean value of the other specimens, which was 333.43±30.22 MPa. The impact test results showed that the lowest impact energy value was found in Specimen C, which is 4.32 Joules, and the highest impact energy value was found in specimens without treatment, which was 15.80 Joules. The microscope observation indicated that the specimen's microstructure was martensite structure increase, and the results of the hardness test were influenced by the martensite phase.